The effect of newcomers’ proactive personality on organizational socialization through information seeking behavior: The moderating effects of team openness and leader behavior - Yoo, JiWoon; Tak, Jinkook (Korean Journal of Industrial and Organizational Psychology, 2012)
The purpose of this study was to examine the relationships among newcomers’ proactive personality, information seeking behavior and organizational socialization. Specifically, This study investigated not only the main effect of newcomers’ proactive personality on information seeking behaviors which related to job and relationship building, and organizational socialization but also the moderating roles of team climate and leader behaviors on the relationships between proactive personality and information seeking behaviors, and between information seeking behaviors and organizational socialization. Online survey was conducted to 151 korean employees working for at least 3 months to 6 months and 151data were obtained for statistical analysis. Three steps of analysis procedures were carried out. First, correlation analysis was conducted and the results showed that there were positive relationship among main variables such as proactive personality, information seeking behavior, organizational socialization and etc. Second, the results of structural equitation model analyses showed that newcomers’ information seeking behaviors fully mediate proactive personality and organizational socialization. Third the results of hierarchial regression analyses showed that while leader behaviors which were specified to feedback behavior and consideration behavior moderated the relationship between information seeking behaviors and organizational socialization, Team openness did not moderate the relationship between proactive personality and information seeking behaviors. The implications and limitations of this study and the directions for future research were discussed on the basis of the results.